The Possibility of Using Rheological and Electrical Properties to Determine the Quality of Craft Wheat Beers - Gorzelany Józef; Hlaváčová Zuzana; Haulíková Ana; Hlaváč Peter; Belcar Justyna (Acta Universitatis Cibiniensis. Series E: Food Technology, 2023)
Beers are among the most popular drinks all over the world. The introduction of beers to the market must be preceded by lengthy physicochemical studies, which are essential to ensure the food safety of consumers. Studying the rheological and electrical properties of beers can not only speed up the product launch, but also improve technological processes. Craft wheat beers enriched with lemongrass and fruit (addition of kamchatka berry and haskap fruits) were used in this study. Beer samples were subjected to density, dynamic viscosity, conductivity and impedance analyses and the values obtained were compared with the results of physicochemical analyses. The coefficient of determination reflects the correctness of the proposed model describing the detected dependence in the best way. The closer its value is to 1, the more accurate the model. The addition of lemongrass extract was found to reduce density, and coefficients of determination had high values in the interval (0.9927 - 0.9961). Beers enriched with berry extract had higher density than the control sample, and coefficients of determination have very high values in the interval (0.9955 - 0.9976). The control beers have the highest conductivity. The lemongrass and fruit extract with which the beer samples were enriched introduced sugar into the beer and these samples had lower conductivity (R2 for beers with lemongrass is situated in interval 0.7772 - 0.9256 and for samples of beers with berries 0.6884 - 0.9846). Based on the impedance, it was possible to distinguish between types of beers, mainly at 50 kHz or 100 kHz.